Complications of total knee arthroplasty - Milovanović Darko; Kadija Marko (Medicinski Podmladak)
Within the last two decades, total knee replacement has become one of the most dominant operating procedures in orthopaedic surgery and traumatology. We witness a growth of the elderly population globally, which results in an increased number of patients with osteoarthritis whose clinical evaluation and subjective concerns require total knee replacement. The majority of patients who underwent surgical procedure are satisfied with the outcome in the long term follow-up period. However, these is still certain percent of patients who underwent surgical procedure who are not satisfied with the outcome. The reasons of dissatisfaction are mostly due to intraoperative and postoperative treatment solutions for surgical complications. The aim of this paperwork is to systematize all potential complications, as well as its diagnostic methods and further treatments in clinical practice. It also aims to highlight possible root causes for these complications in pre-operative selection of patients, intraoperative and post-operative treatment solutions.